Development and Determinants of Corporate Cash Holdings in Germany - Detering, Patrick (2011)
The purpose of this dissertation is to provide an in-depth study of the development and determinants of corporate cash holdings in Germany. We study a sample of 772 companies incorporated in Germany and identify a significant increase in the average ratio of cash-to-assets over the 1987-2010 period. Our work includes a detailed analysis of in-sample differences in the development of cash holdings. We find dissimilarities in the evolution of cash holdings between different company size quartiles, and in relation to dividend status and accounting performance. Further, we detect temporal variations in the evolution of cash holdings for companies considered value and growth stocks and demonstrate differences for individual industries. Moreover, we estimate regression models to identify determinants of corporate cash holdings. Our results are significant for liquid asset substitutes, capital expenditures, leverage, R&D expenditures, and dividend payouts. Overall, we find support for pecking order and trade-off arguments. Moreover, the precautionary motive proves important in explaining the determinants of cash holdings.